2014
DOI: 10.1177/0269216314560009
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of negative pressure wound therapy for a malignant wound legitimate in a palliative context? “The concept of NPWT ad vitam”: A case series

Abstract: We report on our experiences with five patients for whom manufacturers and health authorities contraindicated the use of negative pressure wound therapy because of its potential to encourage tumor growth, although it was considered to be beneficial for all of these patients. This procedure may offer an alternative to conventional wound dressings at the end of life and improve the quality of life of patients by controlling the three most disabling elements: the odor, exudate, and pain associated with changing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 7 publications
0
32
0
2
Order By: Relevance
“…NPWT successfully controlled the odour and obviated the need for frequent painful dressing changes. A subsequent case series validated the use of NPWT in this clinical scenario and concluded that its application results in improved quality of life and earlier discharge to home .…”
Section: Discussionmentioning
confidence: 86%
“…NPWT successfully controlled the odour and obviated the need for frequent painful dressing changes. A subsequent case series validated the use of NPWT in this clinical scenario and concluded that its application results in improved quality of life and earlier discharge to home .…”
Section: Discussionmentioning
confidence: 86%
“…The effect of NPWT in the presence of malignancy is not known. Many human health authorities and manufacturers have contraindicated its use for malignant wounds because of its theoretical potential to promote tumour growth . To our knowledge there are no data in the existing literature to address this concern .…”
Section: Discussionmentioning
confidence: 99%
“…All patients received perioperative cephazolin (22 mg/kg IV; Cephazolin-AFT, AFT Pharmaceuticals, NSW, Aust) followed by cephalexin (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)…”
Section: Postoperative Carementioning
confidence: 99%
“…the sarcomas, the parietal recurrence of the breast carcinoma, the head melanoma described by Riot), which had good results as a palliative treatment in those cases. 4 Heller had introduced vaccum assisted therapy as a preparation for brachytherapy of patients with sarcoma. 5 …”
Section: Discussionmentioning
confidence: 99%
“…2 There are only few contraindications for the negative pressure wound therapy use (e.g. an active malignant process, 3 however, it is reported that in some cases it has achieved positive effects [4][5][6][7][8][9][10] ).…”
Section: Introductionmentioning
confidence: 99%